Integrasi Pendidikan Eco-spiritual: Membangun Kesadaran Pro Lingkungan Hidup Anak Sejak Dini di Islamic Green School Cinere. - Sari, Nila Siska; Sumarna, Lukman (IQ (Ilmu Al-qur'an): Jurnal Pendidikan Islam, 2023)
This study aims to determine the process of strengthening eco-spiritual education programs or activities, orientation of eco-spiritual education activities for students and teachers, and actualization of eco-spiritual education values at SD Al-Ridha Al-Salaam Islamic Green School Cinere. This research is a qualitative research that is field in nature with phenomenological and ecological approaches. This study found that the reinforcement of eco-spiritual education is found in: the integration of curriculum 13 and environmentally sound curriculum, the integration of PAI (certain) materials to environmental insights, and routine activities with environmental insight. There are three orientations of this eco-spiritual educational integration for students, teachers and parents. The application of the integration of eco-spiritual education can be done in various green school programs, such as earth day, market day, and so on.